Village Fund Management: Accountability, Transparency, Community Participation - Andi Syafri Tanete (Program Studi Akuntansi Unimuda Sorong, 2024)
This study aims to determine the effect of accountability, transparency and community participation on the management of funds in Kading Village, Tanete Riaja District, Barru District. The data used in this study are primary data in the form of respondents' assessments of accountability, transparency, community participation and management of village funds. Methods of data collection using questionnaires and literature study. Data analysis techniques using multiple linear regression analysis, t test, F test and coefficient of determination test. The results of the study found that accountability, transparency and community participation had a positive and significant effect on the management of funds for Kading Village, Tanete Riaja District, Barru Regency.